2020
DOI: 10.1177/1729881420929498
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous navigation and obstacle avoidance of an omnidirectional mobile robot using swarm optimization and sensors deployment

Abstract: The present work deals with the design of intelligent path planning algorithms for a mobile robot in static and dynamic environments based on swarm intelligence optimization. Two modifications are suggested to improve the searching process of the standard bat algorithm with the result of two novel algorithms. The first algorithm is a Modified Frequency Bat algorithm, and the second is a hybridization between the Particle Swarm Optimization with the Modified Frequency Bat algorithm, namely, the Hybrid Particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…In formula (7) and (8), r represents the turning radius (radius), L is the turning angle determined by the robot, and the time is t . 1 q and 2 q are the angular velocities of the left and right wheels of the robot, and the constraint equations constrain the angular velocities of the two driving wheels [7] .…”
Section: Hierarchical Fuzzy Obstacle Avoidance Control For Omnidirectmentioning
confidence: 99%
“…In formula (7) and (8), r represents the turning radius (radius), L is the turning angle determined by the robot, and the time is t . 1 q and 2 q are the angular velocities of the left and right wheels of the robot, and the constraint equations constrain the angular velocities of the two driving wheels [7] .…”
Section: Hierarchical Fuzzy Obstacle Avoidance Control For Omnidirectmentioning
confidence: 99%
“…The velocity of each particle is updated according to the following equation [ 42 , 43 ]: where, represents the inertia coefficient, represents the personal acceleration coefficient and represents the social acceleration coefficient. The position of each particle is updated by the equation [ 43 , 44 ]: where and represents the current and updated vectors, respectively.…”
Section: Improvement Of Controllers’ Performances Based On Pso Tecmentioning
confidence: 99%
“…The local path‐planning problem calculates the path while the environment of the mobile robot is continuously changing due to its motion. Whereas, in the global path planning, the environment is entirely known in advance and the terrain must be stationary [11, 12]. Many researchers have investigated the path‐planning problem in dynamic environments, for instance, authors of [13] suggested a novel scheme to choose the best route of the mobile robot by the ant colony optimization (ACO) algorithm in an unknown dynamic environment.…”
Section: Introductionmentioning
confidence: 99%